Electrode paste, electrode layer, all-solid-state battery, and method for producing electrode paste

By combining the electrode active material with hydroxyl groups with fibrous conductive material with acidic functional groups in the electrode slurry of an all-solid battery and performing dispersion treatment, the problem of difficult dispersion of the fibrous conductive material in a low polarity dispersion medium is solved, and the high performance of the electrode layer and the safety and stability of the battery are achieved.

CN119905649APending Publication Date: 2025-04-29TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411456487.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In all-solid batteries, fibrous conductive materials such as carbon nanotubes are prone to form bundled structures, which makes it difficult to fully disperse in a dispersing medium with low polarity, affecting the performance of the electrode layer.

Method used

The electrode slurry is formed by combining the electrode active material with the hydroxyl group with the fibrous conductive material with the acidic functional group and dispersing the process in the dispersion medium. The electrode slurry is added to the first dispersion process and the electrode active material is added to the second dispersion process to improve the dispersion of the fibrous conductive material.

Benefits of technology

Good dispersion of fibrous conductive materials is achieved, the electron conductivity of the electrode layer and the performance of the overall battery are improved, the aggregate of fibrous conductive materials is reduced, and the safety and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905649A_ABST
    Figure CN119905649A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode paste, an electrode layer, an all-solid-state battery, and a method for manufacturing the electrode paste. The main purpose of the present disclosure is to provide an electrode paste in which a fibrous conductive material has good dispersibility. The present disclosure provides an electrode paste for an all-solid-state battery, the electrode paste containing an electrode active material having a hydroxyl group, a fibrous conductive material having an acidic functional group, a solid electrolyte, and a dispersion medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode slurry, an electrode layer, an all-solid battery, and a method for manufacturing the electrode slurry. Background Art

[0002] A fully solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage of being easy to simplify safety devices compared to a liquid battery having an electrolyte containing a flammable organic solvent. As a method for forming an electrode layer (positive electrode layer or negative electrode layer) in a fully solid-state battery, it is known to use an electrode slurry in which an electrode active material, a conductive material, and a solid electrolyte are dispersed in a dispersion medium. Specifically, an electrode layer is obtained by applying and drying the electrode slurry. In addition, although it is not a technology related to fully solid-state batteries, a carbon nanotube dispersion paste containing carbon nanotubes and an organic solvent is disclosed in Patent Document 1.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2023-080910 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In order to suppress the decomposition of the solid electrolyte, the electrode slurry used in the all-solid battery sometimes contains a dispersion medium with low polarity. In addition, fibrous conductive materials such as carbon nanotubes are easy to form a bundle structure. Therefore, even if the fibrous conductive material is dispersed in a dispersion medium with low polarity, it is difficult to fully disperse the fibrous conductive material.

[0008] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide an electrode slurry having good dispersibility of a fibrous conductive material.

[0009] Means for solving problems

[0010] [1] Electrode slurry is an electrode slurry used in all-solid-state batteries, containing an electrode active material having hydroxyl groups, a fibrous conductive material having acidic functional groups, a solid electrolyte, and a dispersion medium.

[0011] [2] The electrode slurry according to [1], wherein the ratio of the hydroxyl group in the electrode active material measured by a CO2-TPD method is 30 μmol / g or more.

[0012] [3] The electrode slurry according to [1] or [2], wherein the ratio of the acidic functional groups in the fibrous conductive material measured by potentiometric reverse titration is 10 μmol / g or more.

[0013] [4] The electrode slurry according to any one of [1] to [3], wherein the electrode active material is a Si-based active material, the fibrous conductive material is a carbon nanotube, and the solid electrolyte is a sulfide solid electrolyte.

[0014] [5] The electrode slurry according to any one of [1] to [4], wherein the slurry particle size is 90 μm or less.

[0015] [6] The electrode slurry according to any one of [1] to [5], wherein when the electrode slurry is applied and dried to form a coating layer, the surface roughness of the coating layer based on ISO25178 is 5 μm or less.

[0016] [7] Electrode layer: an electrode layer used in an all-solid-state battery, comprising an electrode active material having a hydroxyl group, a fibrous conductive material having an acidic functional group, and a solid electrolyte.

[0017] [8] An electrode layer according to [7], wherein when the number of aggregates of the fibrous conductive material having an aspect ratio of greater than 5 and less than 1000 and a long side of greater than 2 μm is confirmed in an area of ​​50 μm×200 μm in a cross section of the electrode layer, the number of the aggregates is less than 10.

[0018] [9] The electrode layer according to [7] or [8], wherein the ratio of the hydroxyl group in the electrode active material measured by a CO2-TPD method is 30 μmol / g or more.

[0019]

[10] The electrode layer according to any one of [7] to [9], wherein the ratio of the acidic functional groups in the fibrous conductive material measured by potentiometric reverse titration is 10 μmol / g or more.

[0020]

[11] The electrode layer according to any one of [7] to

[10] , wherein the electrode active material is a Si-based active material, the fibrous conductive material is a carbon nanotube, and the solid electrolyte is a sulfide solid electrolyte.

[0021]

[12] An all-solid-state battery, comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein at least one of the positive electrode layer and the negative electrode layer is an electrode layer according to any one of [7] to

[11] .

[0022]

[13] The all-solid-state battery according to

[12] , wherein the negative electrode layer is the electrode layer.

[0023]

[14] The all-solid-state battery according to

[13] , wherein the positive electrode layer contains a rock salt layered active material, and the solid electrolyte layer contains a sulfide solid electrolyte.

[0024]

[15] A method for manufacturing an electrode slurry is a method for manufacturing an electrode slurry for an all-solid-state battery, comprising: a first dispersion treatment step, in which an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group are added to a dispersion medium, and a first dispersion treatment is performed to obtain a precursor slurry; and a second dispersion treatment step, in which a solid electrolyte is added to the precursor slurry, and a second dispersion treatment is performed to obtain the electrode slurry.

[0025] Effects of the Invention

[0026] The present disclosure achieves the effect of being able to provide an electrode slurry having a fibrous conductive material with good dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure.

[0028] Figure 2 A schematic diagram for explaining the effects of the present disclosure.

[0029] Figure 3 This is a flow chart illustrating a method for producing an electrode slurry in the present disclosure.

[0030] Figure 4 This is a flow chart illustrating a method for producing an electrode slurry in a reference example.

[0031] Figure 5 : are cross-sectional SEM images of electrode layers obtained in Examples and Reference Examples.

[0032] Description of Reference Numerals

[0033] 1… Positive electrode layer

[0034] 2…Negative electrode layer

[0035] 3…Solid electrolyte layer

[0036] 4…Positive electrode collector

[0037] 5…Negative electrode collector

[0038] 10…All-solid-state batteries DETAILED DESCRIPTION

[0039] The electrode slurry, the electrode layer, the all-solid-state battery, and the method for producing the electrode slurry in the present disclosure are described in detail below.

[0040] A. Electrode slurry

[0041] The electrode slurry in the present disclosure is used to manufacture the electrode layer (positive electrode layer, negative electrode layer) of the all-solid battery. Figure 1 As shown, the all-solid-state battery 10 has a positive electrode layer 1, a negative electrode layer 2, and a solid electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2. The electrode slurry in the present disclosure is generally used to manufacture the positive electrode layer 1 or the negative electrode layer 2. In addition, the electrode slurry in the present disclosure contains: an electrode active material having a hydroxyl group, a fibrous conductive material having an acidic functional group, a solid electrolyte, and a dispersion medium.

[0042] According to the present disclosure, by using an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group in combination, an electrode slurry having good dispersibility of the fibrous conductive material can be obtained. As described above, in order to suppress the decomposition of the solid electrolyte, most electrode slurries used in all-solid batteries contain a dispersion medium with low polarity. In particular, when using a highly reactive solid electrolyte such as a sulfide solid electrolyte, a dispersion medium with low polarity is used. On the other hand, fibrous conductive materials such as carbon nanotubes are prone to form a bundled structure. Therefore, even if the fibrous conductive material is dispersed in a dispersion medium with low polarity, it is difficult to fully disperse the fibrous conductive material.

[0043] In contrast, according to the present disclosure, an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group are used in combination. Figure 2 As shown, the hydroxyl groups on the surface of the electrode active material 11 interact with the acidic functional groups on the surface of the fibrous conductive material 12, thereby suppressing the aggregation of the fibrous conductive materials 12. In the present disclosure, the aggregation (agglomeration) of the fibrous conductive materials 12 is suppressed by using an electrode active material having a hydroxyl group, and in particular, by adopting the method described in "D. Method for producing electrode slurry" described later, the aggregation of the fibrous conductive materials 12 can be more effectively suppressed.

[0044] 1. Electrode active material

[0045] The electrode slurry contains an electrode active material having a hydroxyl group. The presence of a hydroxyl group in the electrode active material can be confirmed by infrared spectroscopy (IR method). Specifically, the peak derived from the OH bond is usually at 3000 cm -1 Above and 3600cm -1 In addition, for example, when the electrode active material is a Si-based active material described later, the peak derived from the Si-O bond is usually at 900 cm -1 Appear nearby.

[0046] The ratio of hydroxyl groups in the electrode active material can be determined by a temperature rise desorption method (CO2-TPD method) using CO2. The ratio of hydroxyl groups in the electrode active material is, for example, 30 μmol / g or more, 40 μmol / g or more, or 50 μmol / g or more. On the other hand, the ratio of hydroxyl groups in the electrode active material is, for example, 150 μmol / g or less.

[0047] As an electrode active material having a hydroxyl group, typically, Si-based active materials can be cited. Si-based active materials are active materials with Si as the main component. Si-based active materials can be Si simple substance, Si alloy, or Si oxide. In addition, Si-based active materials can have a diamond-type crystal phase, can have an inclusion compound type I crystal phase, and can also have an inclusion compound type II crystal phase. In the crystal phase of inclusion compound type I or type II, multiple Si elements form a polyhedron (cage) containing a pentagon or a hexagon. The polyhedron has a space inside that can accommodate (accommodate) metal ions such as Li ions, so the volume change caused by charging and discharging can be suppressed.

[0048] The Si-based active material preferably has a clathrate II-type crystal phase as the main phase. In addition, the composition of the Si-based active material is not particularly limited, but preferably is composed of Na x Si 136 (0≤x≤24). x may be 0 or greater than 0. On the other hand, x may be 20 or less, 10 or less, or 5 or less. The composition of the Si-based active material can be determined, for example, by EDX, XRD, XRF, ICP or atomic absorption spectrometry.

[0049] As other examples of electrode active materials having hydroxyl groups, carbon-based active materials can be listed. Carbon-based active materials are active materials containing inorganic C (carbon) as a main component, for example, graphite can be listed. In addition, as other examples of electrode active materials having hydroxyl groups, active materials containing at least one of Cd, In, Pb, Ga, Ge, Sn, Al, Bi, and Sb can be listed.

[0050] The electrode active material having a hydroxyl group preferably has voids inside the primary particles. The presence of voids inside the primary particles can suppress volume changes caused by charging and discharging. The proportion of voids in the primary particles (void ratio) is, for example, 4% or more, and can be 10% or more. On the other hand, the void ratio is, for example, 40% or less, and can be 20% or less. The void ratio can be determined using, for example, the following steps. First, a cross-section of the electrode active material is observed using a SEM (scanning electron microscope) to obtain a photograph of the particles. Using image analysis software, the solid portion and the void portion are distinguished from the obtained photograph and binarized. The areas of the solid portion and the void portion are determined, and the void ratio (%) is calculated by the following formula.

[0051] Void ratio (%) = 100 × (void area) / ((solid area) + (void area))

[0052] The electrode active material having a hydroxyl group is preferably a Si-based active material (porous Si) having voids inside primary particles.

[0053] The electrode active material may be a positive electrode active material or a negative electrode active material. The shape of the electrode active material is, for example, a particle. The average particle size of the electrode active material is, for example, 0.5 μm or more and 30 μm or less, for example, 0.5 μm or more and 15 μm or less. In the present disclosure, the average particle size refers to the volume cumulative particle size D measured by a laser diffraction scattering particle size distribution measuring device. 50 The proportion of the electrode active material in the solid content of the electrode slurry is not particularly limited, and may be, for example, 10 wt % to 90 wt %, 30 wt % to 80 wt %, or 50 wt % to 70 wt %.

[0054] 2. Fibrous conductive materials

[0055] The electrode slurry contains a fibrous conductive material having an acidic functional group. Examples of the acidic functional group include a carboxyl group (-COOH) and a nitro group (-NO2). Infrared spectroscopy (IR) can be used to confirm that the fibrous conductive material has an acidic functional group. For example, the presence of a peak from an OH bond (at 3000 cm -1 Above and 3600cm -1 The peaks appearing in the range below 1500 cm-1 and the peaks derived from the C=O bond (at 1500 cm-1 -1 Over 1800cm -1 It was confirmed that the fibrous conductive material had a carboxyl group (-COOH).

[0056] The ratio of the acidic functional group in the fibrous conductive material can be obtained by potentiometric reverse titration. The ratio of the acidic functional group in the fibrous conductive material is, for example, 10 μmol / g or more, 30 μmol / g or more, or 50 μmol / g or more. It should be noted that acetylene black (AB), which is a particulate conductive material, sometimes has an acidic functional group (carboxyl group), but its ratio is about 5 μmol / g.

[0057] As the material of the fibrous conductive material with acidic functional groups, for example, carbon materials, metallic materials, conductive resin materials can be listed, wherein preferred carbon materials. This is because electronic conductivity, lightness and durability are excellent. As the fibrous conductive material with acidic functional groups, for example, carbon nanotubes (CNT) and carbon nanofibers (CNF) can be listed. Carbon nanotubes (CNT) can be single-layer carbon nanotubes (SWCNT) or multi-layer carbon nanotubes (MWCNT).

[0058] The aspect ratio (long side / short side) of the fibrous conductive material having an acidic functional group is not particularly limited, and is, for example, 2 or more and 1000 or less, 10 or more and 750 or less, or 50 or more and 500 or less. The length of the long side of the fibrous conductive material is not particularly limited, and is, for example, 0.1 μm or more and 80 μm or less, or 0.5 μm or more and 60 μm or less. On the other hand, the length of the short side of the fibrous conductive material is not particularly limited, and is, for example, 0.5 nm or more and 100 nm or less, or 1 nm or more and 30 nm or less.

[0059] The electrode slurry may contain a fibrous conductive material without an acidic functional group in addition to the fibrous conductive material having an acidic functional group, and may also contain a particulate conductive material. Examples of the particulate conductive material include acetylene black (AB), Ketjen black (KB) and other particulate carbon materials. The proportion of the fibrous conductive material having an acidic functional group relative to all the conductive materials contained in the electrode slurry is, for example, 50% by weight or more, 70% by weight or more, or 90% by weight or more.

[0060] The ratio of the fibrous conductive material having an acidic functional group in the solid content of the electrode slurry is not particularly limited, and may be, for example, 0.05 wt % to 5 wt %, or 0.1 wt % to 3 wt %.

[0061] 3. Solid Electrolyte

[0062] The electrode slurry contains a solid electrolyte. The solid electrolyte is usually an inorganic solid electrolyte. As an inorganic solid electrolyte, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, and a halide solid electrolyte can be listed, among which a sulfide solid electrolyte is preferred. This is because the ion conductivity of the sulfide solid electrolyte is high. In addition, the reactivity of the sulfide solid electrolyte is high, so it is necessary to use a dispersion medium with low polarity. Even in the case of using a dispersion medium with low polarity, by combining an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group, an electrode slurry with good dispersibility of the fibrous conductive material can be obtained.

[0063] The sulfide solid electrolyte usually contains at least Li and S. The sulfide solid electrolyte preferably further contains M element (M is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In). In addition, the sulfide solid electrolyte may contain halogen elements such as F, Cl, Br, and I.

[0064] The sulfide solid electrolyte may be a glass-based (amorphous) sulfide solid electrolyte, a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. The sulfide solid electrolyte may have a crystalline phase. Examples of the crystalline phase include a Thio-LISICON type crystalline phase, an Argentum type crystalline phase, and an LGPS type crystalline phase.

[0065] The composition of the sulfide solid electrolyte is not particularly limited, and examples thereof include xLi2S·(1-x)P2S5(0.5≤x<1), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.5≤x<1, 0≤y≤30, 0≤z≤30). In these compositions, x preferably satisfies 0.7≤x≤0.8.

[0066] Other examples of the composition of the sulfide solid electrolyte include Li 4-x M 1-x P x S4 (0<x<1). M is at least one of Al, Zn, In, Ge, Si, Sn, Sb, Ga and Bi. In addition, a part of Li can be replaced by at least one of Na, K, Mg, Ca and Zn. In addition, as other examples of the composition of the sulfide solid electrolyte, Li 7-x-2y PS 6-x-y X y X is at least one of F, Cl, Br, and I, and x and y satisfy 0≤x, 0≤y. In addition, a portion of Li may be replaced by at least one of Na, K, Mg, Ca, and Zn. Furthermore, a portion of S may be replaced by oxygen (O).

[0067] The shape of the solid electrolyte is, for example, particulate. The average particle size of the solid electrolyte is, for example, 0.1 μm or more and 30 μm or less, and may be 0.5 μm or more and 15 μm or less. In addition, the proportion of the solid electrolyte in the solid component of the electrode slurry is not particularly limited, and may be, for example, 10% by weight or more and 70% by weight or less, 20% by weight or more and 60% by weight or less, or 30% by weight or more and 50% by weight or less.

[0068] 4. Dispersion medium

[0069] The electrode slurry contains a dispersion medium. The dispersion medium preferably has a low polarity. This is because the degradation of the solid electrolyte (especially the sulfide solid electrolyte) can be suppressed. The polarity of the dispersion medium can be specified, for example, according to the Hansen solubility parameter. Specifically, the dispersion medium preferably has a polar term δP of the Hansen solubility parameter of 4 or less. The polar phase δP of the Hansen solubility parameter can be obtained from Hansen Solubility Parameters: A user's handbook, Second Edition. Boca Raton, Fla: CRC Press. (Hansen, Charles (2007)).

[0070] As the dispersion medium, for example, butyl butyrate (δP=2.9), heptane (δP=0), diisobutyl ketone (δP=3.7), tetralin (δP=2), mesitylene (δP=0.6), dibutyl ether (δP=3.4), decane (δP=0), toluene (δP=1.4) can be listed. The electrode slurry may contain only one dispersion medium, or may contain two or more dispersion media. In addition, there is no particular limitation on the solid content concentration of the electrode slurry, for example, it is 30% by weight or more and 70% by weight or less, and may be 40% by weight or more and 60% by weight or less.

[0071] 5. Electrode slurry

[0072] The electrode slurry may further contain a binder. Examples of the binder include fluoride-based binders such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, and fluororubber; and rubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, and ethylene propylene rubber.

[0073] From the viewpoint of dispersibility, the slurry particle size of the electrode slurry is preferably smaller. The slurry particle size of the electrode slurry is, for example, 90 μm or less, 80 μm or less, 60 μm or less, or 40 μm or less. On the other hand, the slurry particle size of the electrode slurry is, for example, 5 μm or more. The slurry particle size of the electrode slurry can be determined based on JIS K5600-2-5.

[0074] In addition, when the electrode slurry is applied and dried to form a coating layer, the surface roughness of the coating layer (surface roughness based on ISO25178) is preferably small from the viewpoint of dispersibility. The surface roughness of the coating layer is, for example, 5 μm or less, 3 μm or less, or 1 μm or less. For the coating layer to be measured, the electrode slurry is preferably formed by knife coating with a gap of 100 μm and drying.

[0075] The method for producing the electrode slurry is not particularly limited, and examples thereof include the method described in “D. Method for producing electrode slurry” described later.

[0076] B. Electrode layer

[0077] The electrode layer in the present disclosure is used for an all-solid-state battery, and contains: an electrode active material having a hydroxyl group, a fibrous conductive material having an acidic functional group, and a solid electrolyte.

[0078] According to the present disclosure, by using a combination of an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group, an electrode layer having good dispersibility of the fibrous conductive material is formed. The electrode active material, the fibrous conductive material and the solid electrolyte are the same as those described in the above "A. Electrode slurry".

[0079] The electrode layer may be a positive electrode layer containing a positive electrode active material, or may be a negative electrode layer containing a negative electrode active material. In addition, when the cross section of the electrode layer is preferably observed, the number of aggregates of the fibrous conductive material is small. Specifically, in the case where the number of aggregates of the fibrous conductive material having an aspect ratio of 5 or more and 1000 or less and a long side of 2 μm or more is confirmed in a region of 50 μm×200 μm, the number of aggregates is, for example, 10 or less, 8 or less, 5 or less, or 3 or less.

[0080] The thickness of the electrode layer is not particularly limited, for example, it is 0.1 μm or more and 1000 μm or less, it can be 0.1 μm or more and 500 μm or less, it can be 0.1 μm or more and 100 μm or less. In addition, as a method for forming the electrode layer, for example, a method of applying and drying the electrode slurry can be cited. The electrode layer is generally used in all-solid batteries. In addition, the present disclosure can also provide a battery component having at least an electrode layer for an all-solid battery.

[0081] C. All-solid-state battery

[0082] Figure 1 This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure. Figure 1 The all-solid-state battery 10 shown has: a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 arranged between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, and a negative electrode collector 5 for collecting current from the negative electrode layer 2. In the present disclosure, at least one of the positive electrode layer 1 and the negative electrode layer 2 is the electrode layer described in the above-mentioned "B. Electrode layer".

[0083] According to the present disclosure, by using the above-mentioned electrode layer, an all-solid-state battery with low resistance can be obtained.

[0084] 1. Positive electrode layer and negative electrode layer

[0085] In the present disclosure, the positive electrode layer may be the electrode layer described above, the negative electrode layer may be the electrode layer described above, and both the positive electrode layer and the negative electrode layer may be the electrode layers described above. The positive electrode layer contains at least a positive electrode active material.

[0086] For example, when the negative electrode layer is the above-mentioned electrode layer, the type of positive electrode active material contained in the positive electrode layer is not particularly limited. Examples of positive electrode active materials include oxide active materials. Examples of oxide active materials include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.8 Co 0.15 Al 0.05 O2 and other rock salt layered active materials; LiMn2O4, Li4Ti5O 12 、Li(Ni 0.5 Mn 1.5 )O4 and other spinel active materials; LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and other olivine active materials.

[0087] A coating containing a Li ion conductive oxide can be formed on the surface of the oxide active material. This is because the reaction between the oxide active material and the solid electrolyte (particularly a sulfide solid electrolyte) can be suppressed. As a Li ion conductive oxide, for example, LiNbO3 can be cited. The thickness of the coating is, for example, not less than 1 nm and not more than 30 nm.

[0088] For example, when the positive electrode layer is the above-mentioned electrode layer, the type of negative electrode active material contained in the negative electrode layer is not particularly limited. Examples of negative electrode active materials include metal active materials such as Li and Sn; carbon active materials such as graphite; and oxide active materials such as lithium titanate.

[0089] The positive electrode layer may further contain at least one of a solid electrolyte, a conductive material, and a binder in addition to the positive electrode active material. Similarly, the negative electrode layer may further contain at least one of a solid electrolyte, a conductive material, and a binder in addition to the negative electrode active material. The solid electrolyte, the conductive material, and the binder are the same as those described in the above-mentioned "A. Electrode slurry".

[0090] 2. Solid electrolyte layer

[0091] The solid electrolyte layer is a layer disposed between the positive electrode layer and the negative electrode layer, and contains at least a solid electrolyte. The solid electrolyte layer may further contain a binder. The solid electrolyte and the binder are the same as those described in the above-mentioned "A. Electrode slurry", so the description here is omitted. In addition, the thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less, 0.1 μm or more and 500 μm or less, or 0.1 μm or more and 100 μm or less.

[0092] 3. Other components

[0093] The all-solid battery in the present disclosure preferably has a positive electrode current collector for collecting the positive electrode layer and a negative electrode current collector for collecting the negative electrode layer. As the material of the positive electrode current collector, for example, SUS, aluminum, nickel, iron, titanium and carbon can be listed. On the other hand, as the material of the negative electrode current collector, for example, SUS, copper, nickel and carbon can be listed.

[0094] The all-solid battery in the present disclosure may further have a constraint fixture for imparting a constraint pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. By using the constraint fixture, a good ion conduction path and a good electron conduction path are formed. The constraint pressure is, for example, above 0.1 MPa, may be above 1 MPa, may be above 5 MPa. On the other hand, the constraint pressure is, for example, below 100 MPa, may be below 50 MPa, may be below 20 MPa.

[0095] 4. All-solid-state batteries

[0096] The type of all-solid-state battery in the present disclosure is not particularly limited, typically a lithium-ion secondary battery. In addition, as the purpose of the all-solid-state battery, for example, the power supply of vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be listed. In particular, it is preferably used for the driving power supply of hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or electric vehicles (BEV). In addition, the all-solid-state battery can be used as a power supply for mobile bodies (such as railways, ships, aircraft) other than vehicles, and can also be used as a power supply for electrical products such as information processing devices. In addition, the manufacturing method of the all-solid-state battery is not particularly limited, and known methods can be used.

[0097] D. Method for manufacturing electrode slurry

[0098] Figure 3 Flow chart of the method for manufacturing the electrode slurry in the present disclosure is shown as an example. Figure 3As shown, an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group are added to a dispersion medium, and a first dispersion treatment is performed to obtain a precursor slurry (a first dispersion treatment step). Next, a solid electrolyte is added to the obtained precursor slurry, and a second dispersion treatment is performed to obtain an electrode slurry (a second dispersion treatment step).

[0099] According to the present disclosure, in the first dispersion treatment step, the electrode active material having hydroxyl groups and the fibrous conductive material having acidic functional groups are dispersed simultaneously, and then, after adding the solid electrolyte, the second dispersion treatment is performed, thereby obtaining an electrode slurry with good dispersibility of the fibrous conductive material.

[0100] 1. First dispersion treatment step

[0101] The first dispersion treatment step is a step of adding an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group to a dispersion medium, performing a first dispersion treatment, and obtaining a precursor slurry. The dispersion medium, the electrode active material having a hydroxyl group, and the fibrous conductive material having an acidic functional group are the same as those described in the above-mentioned "A. Electrode slurry".

[0102] In the first dispersion treatment process, the first dispersion treatment is performed for the dispersion liquid to which the electrode active material having hydroxyl group and the fibrous conductive material having acidic functional group are added in the dispersion medium. For the dispersion medium, a binder can be further added. That is, the first dispersion treatment can be performed for the dispersion liquid containing the electrode active material, the fibrous conductive material and the binder. On the other hand, the first dispersion treatment can be performed for the dispersion liquid containing the electrode active material and the fibrous conductive material, and then, a binder is added in the dispersion liquid to perform additional dispersion treatment. The additional dispersion treatment is preferably performed before the second dispersion treatment process described later.

[0103] As the first dispersion treatment, for example, ultrasonic dispersion treatment and stirring treatment can be cited. The treatment time of the first dispersion treatment is not particularly limited, for example, it is from 1 minute to 60 minutes, and can be from 3 minutes to 30 minutes. The temperature during the first dispersion treatment is not particularly limited, for example, it is room temperature.

[0104] 2. Second dispersion treatment process

[0105] The second dispersion treatment step is a step of adding a solid electrolyte to the precursor slurry and performing a second dispersion treatment to obtain an electrode slurry. The solid electrolyte is the same as described in the above "A. Electrode slurry".

[0106] In the second dispersion treatment step, a solid electrolyte is added to the precursor slurry to perform the second dispersion treatment. A binder may be further added to the precursor slurry to which the solid electrolyte is added to perform the second dispersion treatment.

[0107] As the second dispersion treatment, for example, ultrasonic dispersion treatment and stirring treatment can be listed. The treatment time of the second dispersion treatment is not particularly limited, for example, it is more than 1 minute and less than 60 minutes, and can be more than 3 minutes and less than 30 minutes. The temperature during the second dispersion treatment is not particularly limited, for example, it is room temperature.

[0108] 3. Electrode slurry

[0109] The electrode slurry obtained through the above steps is the same as described in the above “A. Electrode slurry”.

[0110] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any technical solution having substantially the same structure and achieving the same effect as the technical concept described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.

[0111] Example

[0112] [Example 1]

[0113] (Preparation of negative electrode slurry)

[0114] according to Figure 3 Specifically, 0.002 g of single-walled carbon nanotubes (SWCNT, length: 5 μm, fiber diameter: 3 nm, carboxyl ratio: 55 μmol / g) with carboxyl groups, and porous Si (D 50 : 500nm, specific surface area: 50m 2 / g, hydroxyl ratio: 56μmol / g) 1g, and a binder solution (a diisobutyl ketone solution containing PVDF-HFP at a concentration of 5 wt%) 0.8g, and ultrasonic treatment (first dispersion treatment) was performed under the conditions of amplitude 40μm, frequency 20kHz, and 3 minutes to obtain a precursor slurry. Then, 1.2g of a sulfide solid electrolyte (Li3PS4-based glass ceramics containing LiI and LiBr) was added to the obtained precursor slurry, and ultrasonic treatment (second dispersion treatment) was performed under the conditions of amplitude 40μm, frequency 20kHz, and 3 minutes to obtain a negative electrode slurry.

[0115] (Production of negative electrode)

[0116] The obtained negative electrode slurry was applied to a roughened Ni foil (negative electrode current collector) with a doctor blade at a gap of 340 μm and dried, thereby obtaining a negative electrode having a negative electrode current collector and a negative electrode layer.

[0117] (Fabrication of Solid Electrolyte Layer)

[0118] 0.4 g of sulfide solid electrolyte (Li3PS4 glass ceramic containing LiI and LiBr) and 0.05 g of binder solution (heptane solution containing acrylonitrile-butadiene rubber at a concentration of 5 wt%) were added to 0.8 g of heptane, and ultrasonic treatment was performed under the conditions of amplitude 40 μm, frequency 20 kHz, and 10 minutes to obtain slurry. The obtained slurry was applied to a stainless steel foil (substrate) with a gap of 50 μm by a doctor blade and dried. Thus, a transfer member having a substrate and a solid electrolyte layer was obtained.

[0119] (Production of positive electrode)

[0120] Add the positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 O2, NCA) 2g, multilayer carbon nanotubes (MWCNT) 0.03g, sulfide solid electrolyte (Li3PS4 glass ceramics containing LiI and LiBr) 0.3g, binder solution (butyl butyrate solution containing PVDF-HFP at a concentration of 5 weight%) 0.3g, under the conditions of amplitude 40μm, frequency 20kHz, 10 minutes, ultrasonic treatment was performed to obtain a positive electrode slurry. The obtained positive electrode slurry was applied to Al foil (positive electrode collector) with a gap of 300μm by a scraper and dried. Thus, a positive electrode having a positive electrode collector and a positive electrode layer was obtained.

[0121] (Battery production)

[0122] In a manner that the negative electrode layer in the negative electrode is relative to the solid electrolyte layer in the transfer member, the negative electrode and the transfer member are overlapped, and roller pressing is performed under the conditions of line pressure 3t / cm and room temperature to obtain a negative electrode laminate. Similarly, in a manner that the positive electrode layer in the positive electrode is relative to the solid electrolyte layer in the transfer member, the positive electrode and the transfer member are overlapped, and roller pressing is performed under the conditions of line pressure 4t / cm and room temperature to obtain a positive electrode laminate. Then, in a manner that the solid electrolyte layers are relative to each other, the positive electrode laminate and the negative electrode laminate are overlapped, and the solid electrolyte layers are joined to each other. Thus, a battery is obtained.

[0123] [Examples 2 to 5]

[0124] A negative electrode slurry was obtained in the same manner as in Example 1 except that the particle size and specific surface area of ​​porous Si were changed to the values ​​shown in Table 1. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0125] [Example 6]

[0126] A negative electrode slurry was obtained in the same manner as in Example 1 except that multiwalled carbon nanotubes having carboxyl groups (MWCNT, length: 5 μm, fiber diameter: 150 nm, carboxyl group ratio: 60 μmol / g) were used instead of SWCNT. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0127] [Examples 7 to 10]

[0128] A negative electrode slurry was obtained in the same manner as in Example 6 except that the particle size and specific surface area of ​​porous Si were changed to the values ​​shown in Table 1. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0129] [Example 11]

[0130] A negative electrode slurry was obtained in the same manner as in Example 1, except that solid Si nanoparticles were used instead of porous Si. A battery was obtained in the same manner as in Example 1, except that the obtained negative electrode slurry was used.

[0131] [Examples 12 and 13]

[0132] A negative electrode slurry was obtained in the same manner as in Example 1 except that the particle size and specific surface area of ​​the Si nanoparticles were changed to the values ​​shown in Table 1. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0133] [Example 14]

[0134] Except that solid Si nanoparticles were used instead of porous Si, a negative electrode slurry was obtained in the same manner as in Example 6. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0135] [Reference Example 1]

[0136] according to Figure 4The negative electrode slurry was prepared according to the process shown. Specifically, 0.002g of SWCNT and 0.8g of binder solution were added to 2.7g of diisobutyl ketone as a dispersion medium, and ultrasonic treatment (dispersion treatment X) was performed under the conditions of amplitude 40μm, frequency 20kHz, and 3 minutes to obtain a first precursor slurry. Then, 1g of porous Si was added to the obtained first precursor slurry, and ultrasonic treatment (dispersion treatment Y) was performed under the conditions of amplitude 40μm, frequency 20kHz, and 3 minutes to obtain a second precursor slurry. Then, 1.2g of sulfide solid electrolyte was added to the obtained second precursor slurry, and ultrasonic treatment (dispersion treatment Z) was performed under the conditions of amplitude 40μm, frequency 20kHz, and 3 minutes to obtain a negative electrode slurry. It should be noted that the materials used for the negative electrode slurry are the same as those in Example 2. In addition, except for using the obtained negative electrode slurry, a battery was obtained in the same manner as in Example 1.

[0137] [Reference Example 2]

[0138] A negative electrode slurry was obtained in the same manner as in Reference Example 1 except that MWCNT used in Example 6 was used instead of SWCNT. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0139] [Reference Example 3]

[0140] Except that solid Si nanoparticles were used instead of porous Si, a negative electrode slurry was obtained in the same manner as in Reference Example 1. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0141] [Reference Example 4]

[0142] Except that solid Si nanoparticles were used instead of porous Si, a negative electrode slurry was obtained in the same manner as in Reference Example 2. A battery was obtained in the same manner as in Example 1 except that the obtained negative electrode slurry was used.

[0143]

Table 1

[0144]

[0145] [evaluate]

[0146] (Slurry particle size)

[0147] The negative electrode slurries prepared in Examples 1 to 14 and Reference Examples 1 to 4 were used to measure the slurry particle size. Specifically, the slurry particle size was measured based on JIS K5600-2-5. The results are shown in Table 2.

[0148] (Surface roughness based on ISO25178)

[0149] The negative electrode slurry prepared in Examples 1 to 14 and Reference Examples 1 to 4 was applied to the roughened Ni foil with a 100 μm gap scraper and dried. Thus, an evaluation sample was obtained. The surface of the obtained evaluation sample was measured using a digital microscope (VHX-8000 manufactured by KEYENCE) in a 500-fold field of view, and the surface roughness based on ISO25178 was obtained. The results are shown in Table 2.

[0150] (Battery cell resistance)

[0151] The resistance of the batteries obtained in Examples 1 to 14 and Reference Examples 1 to 4 was measured. Specifically, the batteries were charged with CCCV at C / 10 until 4.35 V. Then, CCCV discharge was performed at C / 3 until 3.35 V. Then, discharge was further performed at 7C, and the battery cell resistance was calculated from the voltage change and current value in 10 seconds. The results are shown in Table 2.

[0152] (Electronic conductivity)

[0153] The electron conductivity was measured using the negative electrodes prepared in Examples 1 to 14 and Reference Examples 1 to 4. Specifically, the negative electrodes were punched into 1 cm 2 The two punched negative electrodes were stacked so that the negative electrode layers faced each other. The stacked body was restrained in the thickness direction, and the resistance was measured to find the electronic conductivity. The results are shown in Table 2.

[0154] (Number of aggregates)

[0155] Using the negative electrode layers prepared in Examples 1 to 14 and Reference Examples 1 to 4, the number of aggregates of the conductive material was measured. Specifically, the cross section of the negative electrode layer was observed using a scanning electron microscope (SEM, FE-SEM SU-8200 manufactured by Hitachi) at a field of view of 400 times. Then, the number of aggregates of the conductive material having an aspect ratio of greater than 5 and less than 1000 and a long side of greater than 2 μm was confirmed in an area of ​​50 μm×200 μm. This operation was performed 10 times, and the average value was set as the number of aggregates of the conductive material. The results are shown in Table 2. In addition, as Figure 5 As shown in (a), almost no aggregates of the conductive material were confirmed in the negative electrode layer prepared in Example 1. Figure 5 As shown in (b), a plurality of aggregates (parts surrounded by black circles) were confirmed in the negative electrode layer prepared in Reference Example 1.

[0156]

Table 2

[0157]

[0158] As shown in Table 1, it was confirmed that the dispersibility of the fibrous conductive material in the electrode slurries of Examples 1 to 14 and Reference Examples 1 to 4 was good. Thus, by using the electrode active material having a hydroxyl group and the fibrous conductive material having an acidic functional group in combination, an electrode slurry having a good dispersibility of the fibrous conductive material was obtained.

[0159] Among them, it was confirmed that Examples 1 to 5 had smaller slurry particle size, smaller surface roughness, smaller battery cell resistance, higher electron conductivity, and fewer aggregates than Reference Example 1. Similarly, it was confirmed that Examples 6 to 10 had smaller slurry particle size, smaller surface roughness, smaller battery cell resistance, higher electron conductivity, and fewer aggregates than Reference Example 2. Thus, it was confirmed that in the present disclosure, simultaneous dispersion is preferred over sequential dispersion. In addition, based on the above results, in the present disclosure, the average particle size D of porous Si is 50 The average particle size D of porous Si is preferably 300 nm or more and 1200 nm or less. 50 It can be 500 nm or more and 1000 nm or less. In addition, in the present disclosure, the specific surface area of ​​porous Si is preferably 30 m 2 / g and above 800m 2 / g or less. The specific surface area of ​​porous Si can be 50m 2 / g and above 600m 2 / g or less.

[0160] In addition, it was confirmed that Example 11 had a smaller slurry particle size, a smaller surface roughness, a smaller battery cell resistance, a higher electron conductivity, and a smaller number of aggregates than Reference Example 3. In addition, it was confirmed that Example 14 had a smaller slurry particle size, a smaller surface roughness, a smaller battery cell resistance, a higher electron conductivity, and a smaller number of aggregates than Reference Example 4. In addition, based on the results of Examples 11 and 12, in the present disclosure, the particle size D of the Si nanoparticles 50 The average particle size of Si nanoparticles is preferably less than 100 nm. 50 On the other hand, the average particle size D of Si nanoparticles is 80 nm or less, and 60 nm or less. 50 In addition, in the present disclosure, the specific surface area of ​​Si nanoparticles is preferably greater than 20 nm. 2 / g. The specific surface area of ​​Si nanoparticles can be 30m 2 / g or above, can be 40m 2 / g or more. On the other hand, the specific surface area of ​​Si nanoparticles can be 70m 2 / g or less.

Claims

1. Electrode slurry is an electrode slurry used for all-solid-state batteries, containing an electrode active material having hydroxyl groups, a fibrous conductive material having acidic functional groups, a solid electrolyte and a dispersion medium.

2. The electrode slurry according to claim 1, wherein The ratio of the hydroxyl group in the electrode active material measured by a CO2-TPD method is 30 μmol / g or more.

3. The electrode slurry according to claim 1, wherein: The ratio of the acidic functional group in the fibrous conductive material measured by potentiometric reverse titration is 10 μmol / g or more.

4. The electrode slurry according to claim 1, wherein The electrode active material is a Si-based active material, the fibrous conductive material is a carbon nanotube, and the solid electrolyte is a sulfide solid electrolyte.

5. The electrode slurry according to claim 1, wherein The slurry particle size is less than 90 μm.

6. The electrode slurry according to claim 1, wherein When the electrode slurry is applied and dried to form a coating layer, the coating layer has a surface roughness of 5 μm or less in accordance with ISO 25178.

7. The electrode layer is an electrode layer used for an all-solid-state battery, and contains an electrode active material having a hydroxyl group, a fibrous conductive material having an acidic functional group, and a solid electrolyte.

8. The electrode layer according to claim 7, wherein When the number of aggregates of the fibrous conductive material having an aspect ratio of 5 to 1000 and a long side of 2 μm or more is confirmed in a 50 μm×200 μm region in the cross section of the electrode layer, the number of the aggregates is 10 or less.

9. The electrode layer according to claim 7, wherein The ratio of the hydroxyl group in the electrode active material measured by a CO2-TPD method is 30 μmol / g or more.

10. The electrode layer according to claim 7, wherein The ratio of the acidic functional group in the fibrous conductive material measured by potentiometric reverse titration is 10 μmol / g or more.

11. The electrode layer according to claim 7, wherein The electrode active material is a Si-based active material, the fibrous conductive material is a carbon nanotube, and the solid electrolyte is a sulfide solid electrolyte.

12. An all-solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein at least one of the positive electrode layer and the negative electrode layer is the electrode layer according to any one of claims 7 to 11.

13. The all-solid-state battery according to claim 12, wherein: The negative electrode layer is the electrode layer.

14. The all-solid-state battery according to claim 13, wherein: The positive electrode layer contains a rock salt layered active material, and the solid electrolyte layer contains a sulfide solid electrolyte.

15. A method for producing an electrode slurry, which is a method for producing an electrode slurry for an all-solid-state battery, comprising: The first dispersion treatment step comprises: Adding an electrode active material having a hydroxyl group and a fibrous conductive material having an acidic functional group into a dispersion medium, performing a first dispersion treatment, and obtaining a precursor slurry; and The second dispersion treatment step includes adding a solid electrolyte to the precursor slurry and performing a second dispersion treatment to obtain the electrode slurry.

Citation Information

Patent Citations

  • Carbon nanotube dispersion paste, manufacturing method of carbon nanotube dispersion paste, quality management method for carbon nanotube dispersion paste, mixture paste, electrode for lithium ion battery cathode and lithium ion battery

    JP2023080910A